Is phased implementation of HPV testing and triage with dual staining the way to transform organized cytology screening? - Sláma, Jiří; Dvořák, Vladimír; Trnková, Markéta; Skřivánek, Aleš; Hrabcová, Karolína; Ovesná, Petra; Nováčková, Martina (European journal of cancer prevention, 2024)
OBJECTIVE: The substantial material and legislative investments in establishing and maintaining cytological screening in the Czech Republic represent barriers to a direct transition to primary HPV screening. Therefore, the LIBUSE project was implemented to test the efficacy of phasing in HPV DNA testing as a co-test to cytology in routine screening of women >30 years of age. METHODS: Women aged 30 to 60 years who underwent regular annual Pap smears were co-tested for HPV DNA with selective 16/18 genotyping at 3-year intervals. All HPV 16/18-positive cases and/or cases with a severe abnormality in cytology were sent for colposcopy; HPV non-16/18-positive cases and LSILs were graded using p16/Ki67 dual-stain cytology, and positive cases were sent for colposcopy. RESULTS: Overall, 2409 patients were included. After the first combined screening (year 'zero') visit, 7.4% of women were HPV-positive and 2.0% were HPV16/18-positive; only 8 women had severe Pap smear abnormalities. Triage by dual staining was positive in 21.9% of cases (28/128). Biopsy confirmed 34 high-grade precancer lesions. At the second combined visit (year 'three'), the frequency of HPV infection (5.3% vs. 7.4%) frequency of HPV16/18 (1.1% vs. 2.0%), referrals for colposcopy (35 vs. 83), and biopsy verified high-grade lesions (5 vs. 34) were significantly lower (all P ≤ 0.001). CONCLUSION: The addition of HPV DNA testing with selective genotyping of HPV16/18 to existing cytology screening significantly increased the safety of the program. The gradual introduction of HPV testing was well received by healthcare professionals and patients, and can facilitate transformation of the cytology-based screening. ClinicalTrials.gov Identifier: NCT05578833.
Keywords: dospělí; Female; Papillomavirus Infections; časná detekce nádoru; lidský papilomavirus 16; Papanicolaouův test; Adult; ženské pohlaví; Staining and Labeling; Human papillomavirus 18; DNA; lidé; barvení a značení; nádory děložního čípku; Papanicolaou Test; plošný screening; Triage; infekce papilomavirem; lidský papilomavirus 18; Vaginal Smears; Uterine Cervical Neoplasms; Early Detection of Cancer; vaginální stěr; třídění pacientů; Uterine Cervical Dysplasia; Mass Screening; Human papillomavirus 16; dysplazie děložního hrdla; Humans